2006
DOI: 10.2118/79709-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Techniques for Coupling Porous Flow and Geomechanics

Abstract: Summary This paper compares three techniques for coupling multiphase porous flow and geomechanics. Sample simulations are presented to highlight the similarities and differences in the techniques. One technique uses an explicit algorithm to couple porous flow and displacements in which flow calculations are performed every timestep and displacements are calculated only during selected timesteps. A second technique uses an iteratively coupled algorithm in which flow calculations and displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 12 publications
10
143
0
14
Order By: Relevance
“…Dean et al [21] and Jalali et al [22] compared the fully and iteratively coupled techniques through a series of sensitivity analyses performed on simple case studies. Dean et al [21] also analyzed different convergence criterions for the different coupling schemes and concluded that, if sufficiently tight convergence tolerances were adopted, the fully coupled approach and the iteratively coupled one provided the same results. If the correct convergence criterion is applied, an iteratively coupled method ensures loss of accuracy.…”
Section: Coupling Techniquesmentioning
confidence: 99%
“…Dean et al [21] and Jalali et al [22] compared the fully and iteratively coupled techniques through a series of sensitivity analyses performed on simple case studies. Dean et al [21] also analyzed different convergence criterions for the different coupling schemes and concluded that, if sufficiently tight convergence tolerances were adopted, the fully coupled approach and the iteratively coupled one provided the same results. If the correct convergence criterion is applied, an iteratively coupled method ensures loss of accuracy.…”
Section: Coupling Techniquesmentioning
confidence: 99%
“…The different coupling techniques are briefly presented in the following, highlighting the main advantages and shortcomings of each methodology [3] .…”
Section: Different Degrees Of Couplingmentioning
confidence: 99%
“…Desai and coworkers [3][4][5][6][7] introduced a hierarchical approach for the development of constitutive models to account for various factors that influence the geological material behavior. This approach allows for progressive development of models of higher grades, corresponding to different levels of complexities.…”
Section: Principal Basic Equationsmentioning
confidence: 99%
“…Recent studies focusing on linking numerical coupled fluid-flow and geomechanical simulation with seismic modelling have improved our understanding of the relationship between seismic attributes, fluid properties and mechanical deformation due to reservoir fluid extraction and injection (e.g., Rutqvist et al 2002;Dean et al 2003;Herwanger and Horne 2009;Alassi et al 2010;Herwanger et al 2010;Verdon et al 2011;He et al 2015;Angus et al 2015). Analytic and semi-analytic approaches using poroelastic formulations have previously been used to understand surface subsidence (e.g., Geertsma 1973) and seismic travel-time shifts (e.g., Fuck et al 2010) due to pore pressure changes.…”
Section: Introductionmentioning
confidence: 99%
“…Formulations exist for fully coupled fluid-flow and geomechanical simulation, yet they tend to be computationally expensive (e.g., Minkoff et al 2003). However, iterative and loose coupling of fluid-flow simulators with geomechanical solvers can be more efficient and yield sufficiently accurate results compare to fully coupled solutions (e.g., Dean et al 2003;Minkoff et al 2003). Furthermore, iterative and loosely coupled approaches allow the use of already existing commercial reservoir fluid-flow modelling software.…”
Section: Introductionmentioning
confidence: 99%